Analisis Kinerja Keuangan Berdasarkan Rasio Likuiditas dan Rasio Profitabilitas PT Aneka Tambang Tbk Tahun 2019-2021 - Aurel Priastyca Permata Agustine; Sri Hermuningsih (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to determine the financial performance of PT Aneka Tambang Tbk in 2019-2021 by using the calculation of the liquidity ratio and profitability ratio. The method used in this study is a quantitative descriptive method, namely processing existing company financial data in the form of financial statements and the data used is secondary data sourced from the official website of the Indonesia Stock Exchange, www.idx.co.id and PT. Antam. The results of this study indicates that in 2019 and 2021 PT Antam can be said in a good condition, but in 2020 PT Antam's financial performance is not good. However, the profit obtained by PT Antam from 2019-2021 has always increased.